Implementation of a rapid HIT immunoassay at a university hospital – Retrospective analysis of HIT laboratory orders in patients with thrombocytopenia - Black, Anne; Heimerl, Susanne; Oertli, Linnea; Wilczek, Wolf; Greinacher, Andreas; Spannagl, Michael; Herr, Wolfgang; Hart, Christina (Thrombosis Research, 2017)
Background Heparin-induced thrombocytopenia (HIT) is a rare cause of thrombocytopenia and a potentially life-threatening adverse drug reaction. Clinical overdiagnosis of HIT results in costly laboratory tests and anticoagulation. Criteria and algorithms for diagnosis are established, but their translation into clinical practice is still challenging. Study design and methods In a retrospective approach we studied all HIT related laboratory test requests within four years and evaluated data before (1st period, 24 month) and after (2nd period, 24 month) replacing particle gel immunoassay (PaGIA) and enzyme-linked immunosorbent assay (ELISA) by a chemiluminescent immunoassay (CLIA). HIT was confirmed by heparin-induced platelet activation (HIPA) test. Clinical pretest probability for HIT using an implemented simplified 4Ts score and platelet count were evaluated. Costs for laboratory tests and alternative anticoagulation were calculated. Results In 1850 patients with suspected HIT, 2327 laboratory orders were performed. In 87.2% of these orders an intermediate/high simplified 4Ts score was found. Thrombocytopenia was present in 87.1%. After replacing PaGIA and ELISA by CLIA the number of immunological and functional laboratory tests was reduced by 38.2%. The number of positive HIT immunoassays declined from 22.6% to 6.0%, while the number of positive HIPA tests among positive immunological tests increased by 19%. Altogether, acute HIT was confirmed in 59 patients. A decline in the use of alternative anticoagulants was observed in the 2nd period. Conclusion Our study shows that in a university hospital setting HIT is well-known, but diagnosis requires a precise laboratory confirmation. Replacing PaGIA and ELISA by CLIA did not influence laboratory order behavior but results in reduced overall costs for laboratory diagnostics and alternative anticoagulation.
CRIS-Team Scopus Importer:2023-03-23
Keywords: 4Ts score; HIT; Thrombocytopenia